Dislocation of mandible in 48 year old patient - the continuation of a therapy - Klaudia Brożyna; Jędrzej Tkaczyk; Tomasz Krzysztof Bąk; Jolanta Wojciechowicz; Anna Gawęda; Marcin Baran; Tomasz Tomaszewski (Journal of Education, Health and Sport, 2018)
Dislocation of a temporomandible joint (TMJ) is a rare disfunction, which has multiform background divided into imbalance in the function of neuromascular component or structural deficit. A 48-year-old woman was admitted to the Department of Maxillo-Facial Surgery of the Medical University of Lublin due to continuation of a treatment of TMJ dislocation. Previous hospitalization was performed a few months earlier. Reposition in general anaesthesia was used as a treatment, however it ended up with defeat. Current hospitalization with open surgery reposition was scheduled. Bilateral condylectomy was prosecuted. After surgery correct movability and proper anterior-posterior placement of mandible were achieved.